Hubungan sikap ilmiah dan keterampilan eksperimen terhadap hasil belajar IPA siswa kelas V SDN di Kecamatan Laweyan - Annisa Rizki Isnaini Khomariyah; Jenny Indrastoeti Siti Poerwanti (Universitas Sebelas Maret, 2025)
This study aims to determine whether there is a relationship between scientific attitudes and experimental skills on science learning outcomes. This study was conducted on fifth-grade students at SDN in Laweyan District in the 2024/2025 academic year. The sampling technique used was probability sampling of the cluster random sampling type, employing observation sheets and multiple-choice questions as instruments. Hypothesis testing was conducted using a multiple correlation test to determine the relationship between the three variables. The results showed a correlation coefficient of 0.293 > 0.195, indicating a low-level relationship category, with a correlation between experimental skills and science learning outcomes for fifth-grade students. with a correlation coefficient of 0.513 > 0.195, indicating a moderate level of relationship, and there is a relationship between scientific attitude and experimental skills on the science learning outcomes of fifth-grade students, with a correlation coefficient of 0.603 > 0.195, indicating a strong level of relationship.